Respuestas

¡La mejor respuesta!
  • Usuario de Brainly
2013-12-27T12:52:49+01:00
 \frac{x-2}{8} -  \frac{3*(x+6)}{4} +x = -1

 \frac{x-2}{8} -  \frac{3x+18}{4} +x = -1

Lo pasamos a común denominador:

 \frac{x-2}{8} -  \frac{2*(3x+18)}{8} + \frac{8x}{8} = -1

 \frac{(x-2)-(6x+36)+8x}{8} = -1

{(x-2)-(6x+36)+8x} = -1*8

x-2-6x-36+8x=-8

x-6x+8x = -8+2+36

3x = 30

x =  \frac{30}{3}

x = 10
  • Usuario de Brainly
2013-12-27T14:37:44+01:00
X-2/8 - 3(x+6)/4+x = -1  saco el mcm de 8 y4 que es 8
[(x-2)-6(x+6)+8x]/8=-1
[x-2-6x-36+8x =(-1)*8
3x -38 =-8
3x= -8+38
3x=-30
x=-30/3
x=10